THE REPRESENTATION OF NATIONAL IDENTITY IN THE CONVERSATION BETWEEN DOMESTIC AND FOREIGN TOURISTS AT BATU KARAS, PANGANDARAN - Suroto Suroto (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2016)
The present research focuses on the study of language and tourism. It analyses the discursive strategies and their realization in the conversation between domestic and foreign tourists at Batu Karas, Pangandaran by using Discourse Historical Approach. This study is a qualitative study and data were collected through a participant observation and recording conducted for nearly a week. The results show that the subjects use two discursive strategies of Discourse Historical Approach; nomination and predication to express the topic of national body and culture as the representation of national identity. The nomination strategy is realized in the form of noun while the predication strategy is in the form of adjective and adverb. Meanwhile, two ideologies are reflected from the conversation between domestic and foreign tourists; feudalism and nationalism